Reduction of medium consumption in perfusion mammalian cell cultures using a perfusion rate equivalent concentrated nutrient feed. (24th June 2020) - Bielser, Jean‐Marc; Kraus, Leon; Burgos‐Morales, Orlando; Broly, Hervé; Souquet, Jonathan
Abstract: Media preparation for perfusion cell culture processes contributes significantly to operational costs and the footprint of continuous operations for therapeutic protein manufacturing. In this study, definitions are given for the use of a perfusion equivalent nutrient feed stream which, when used in combination with basal perfusion medium, supplements the culture with targeted compounds and increases the medium depth. Definitions to compare medium and feed depth are given in this article. Using a concentrated nutrient feed, a 1.8‐fold medium consumption (MC) decrease and a 1.67‐fold increase in volumetric productivity (PR) were achieved compared to the initial condition. Later, this strategy was used to push cell densities above 100 × 10 6 cells/ml while using a perfusion rate below 2 RV/day. In this example, MC was also decreased 1.8‐fold compared to the initial condition, but due to the higher cell density, PR was increased 3.1‐fold and to an average PR value of 1.36 g L −1  day −1 during a short stable phase, and versus 0.46 g L −1  day −1 in the initial condition. Overall, the performance improvements were aligned with the given definitions. This multiple feeding strategy can be applied to gain some flexibility during process development and also in a manufacturing set‐up to enable better control on nutrient addition.